Teaching academic writing to Iraqi undergraduate students: An investigation into the effectiveness of a genre-process approach - Al-Asadi, Sami Abbas Naser (Curtin University, 2015)
A modified integrated process-genre approach (MIM) was implemented with EFL undergraduate students in Iraq. Some students subject to the MIM were better able to construct structurally complex and reasonably-grounded arguments and to employ a wider range of informal reasoning patterns group.Combining the merits of both the process and genre approaches has the potential to develop a more coherent model of writing by taking into account cognitive and social demands.